Security and privacy based access control model for internet of connected vehicles - Habib, Muhammad Asif; Ahmad, Mudassar; Jabbar, Sohail; Khalid, Shehzad; Chaudhry, Junaid; Saleem, Kashif; Rodrigues, Joel J.P. C.; Khalil, Muhammad Sayim (Future generation computer systems, 2019)
Vehicular networks are continually gaining popularity, owing to the evolution of the Internet of things, by means of rapid communication in IP-based networks. Vehicles are being fitted with sensory devices to gain inputs from the external environment for information processing. Numerous applications of vehicular networks depend on the use of communication networks. The security and privacy of data communication are significant challenges, particularly in wireless applications, for example, the Internet of connected vehicles. When an official fleet of vehicles (government or military) begins its journey, the vehicles need to communicate with one another to share sensitive information. The security of such a fleet is maintained in various security layers, each of which coordinates and communicates with the others, but avoids disclosing sensitive information of higher security layers to lower security layers. No such access control model exists that can enforce the authority of security officials in layers. We propose a novel security and privacy based access control (SPBAC) model for the Internet of connected vehicles, which allows security officials to access information in combination with permissions and roles, instead of roles only, for officials traveling in vehicles belonging to the same fleet. Vehicle-to-vehicle communication is performed with the aid of onboard unit sensory devices. The vehicles can also communicate through wireless technology, namely WiFi and cellular communications (4G/5G). The SPBAC model provides communication among security layers in a secure, private, and efficient manner compared to other state-of-the-art algorithms. The SPBAC model is demonstrated here using mathematical modeling along with implementation examples. •Research focus on security and privacy of data communication in Internet of Connected Vehicles (IoCV).•An access control model is proposed that allows the access-authorities of security officials in layers.•The vehicles can communicate through wireless technology, i.e. Wi-Fi and cellular communication (4G/5G).•The proposed model ensures security, private and an efficient communication.•The model is demonstrated by using mathematical modeling along with implementation.